The Effect Of Interval Giving ZPT Hantu And Growmore Fertilizer On Grafting Growth Of Citrus Plants (Citrus Sp) - erti, Erti kumala indah; Mukhlis (Jurnal Online Pertanian Tropik, 2023)
ABSTRACT This research aims to determine the effect of ZPT Hantu and Fertilizer Gromore on the growth of citrus plant grafting (Citrus sp). The experimental design used in this study was a Randomized Block Design (RAK) with two factors, namely ZPT Hantu and Fertilizer Growmore. The results of statistical analysis showed that the ZPT Hantu treatment on the growth of shoot height at the age of 5 weeks, 7 weeks, 9 weeks and 11 weeks, stem diameter parameters at 5 weeks, 7 weeks, 9 weeks, the number of stalks at the age of 5 weeks, 7 weeks. significant effect on thebut diameter of 11 Weeks After Planting and leaf area parameters of 11 Weeks After Planting. The results of statistical analysis showed that. Growmore fertilizer was applied to the parameters of shoot height at the age of 5 weeks, 7 weeks, 9 weeks and 11 weeks, stem diameter at 5 weeks, 7 weeks, 9 weeks and 11 weeks, the number of leaf stalks at 5 Weeks After Planting, 7 Weeks After Planting, 9 Weeks After Planting and 11 Weeks After Planting, the parameter of leaf area at 11 Weeks After Planting showed no significant effect. The results of statistical analysis showed that the interaction between the two treatments showed aninsignificant effect on the parameters of bud height, stem diameter, number of stalks and leaf area.